Arm-wave display in a liolaemus lizard - Vicente, Natalin Soledad (2019)
Lizards show a great variety of visual displays. Among them, arm-waving is a behaviour that has received little attention and its role is still controversial. Here, I analyse the armwaves of Liolaemus pacha lizards in their natural habitat with the aim of determining their function. Arm-waving was performed by both sexes, usually with the ventral body surface in contact with the ground. Furthermore, it was more frequent when alone, and during female-male interactions. The results of this study are suggestive but not conclusive regarding the possible function of this behaviour.